Telecommunications Reform in Uganda - Shirley, Mary M.; Tusubira, F.F.; Gebreab, Frew; Haggarty, Luke (World Bank, Washington, DC, 2014)
The paper documents the case of Uganda's telecommunications reform. Uganda is one of only two countries in Africa that decided to privatize telecommunications in a competitive framework by selling a second national operator license. The authors find that Uganda did not sacrifice significant sales proceeds by choosing competition, but instead gained tremendously in both the speed and scale of investment from its early focus on competition.